Geochemical characteristics and significance of aromatic hydrocarbons in crude oil from the East Fukang Sag, Junggar Basin, NW China - Li, Yan; Hou, Dujie; Cheng, Xiong; Han, Xu; Niu, Congkai (Frontiers in Earth Science, 2023)
The aromatic compounds of twenty crude oil samples from different formations in the East Fukang Sag were studied by the gas chromatography–mass spectrometry technique. Through analysis of the composition of the main aromatic hydrocarbons, the studied crude oil samples were generally divided into two types: Oil type Ⅰ had the relatively high content of the naphthalene series, biphenyl series and dibenzofuran series, while the samples from Oil type Ⅱ contained relatively high abundance of phenanthrene series, fluorene series, triaromatic steroid series, and obvious methyltrimethyltridecylchromans. The geochemical parameters reflecting the source and sedimentary environment in naphthalene series, phenanthrene series, biphenyl series, three-fluorene series, and triaromatic steroid series were systematically analyzed. Analysis of the results showed that studied oil samples from the East Fukang Sag were of continental origin and deposited in a weakly oxidizing to weakly reducing environment with fresh-brackish water. Oil type Ⅰ was characterized by considerably abundant terrestrial higher plant organic matter inputs, while Oil type Ⅱ was typical with obviously lower aquatic organisms. Maturity-related parameters calculated from alkyl naphthalenes, alkyl phenanthrenes, alkyl dibenzothiophenes, and methyltrimethyltridecylchromans showed that all the studied oil samples have reached the mature stage.